Teacher Retention and Turnover: Exploring the Factors that Influence Teacher Decision-Making - Aulia, Nurul; Haerani, Ira (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
Teacher attrition and mobility are important concerns for educators in global Education systems especially in Third world country like Indonesia. This study explores the multifaceted factors that influence teachers' decisions to stay in or leave their positions, focusing on five key themes: Thus, the following compensation and benefits factors were issued: Working Conditions, School Environment Support, Personal and Family Circumstances, and Professional Development and Promotion. According to this study with the collected data of interviews and focus group discussion with thirty teachers in Indonesia the find that the reasons for teacher turnover include low remuneration, poor working condition, lack of school culture support, time and family demands and limited professional development. The present study shows that there are numerous and quite varied factors, which require a multi-faceted approach to retaining teachers. Increasing salaries and benefits, developing the working context, maintaining a positive organisational climate, meeting teachers’ personal needs and continuous professional learning help educational systems to lower high teacher turnover rates and develop beneficial educational outcomes. In the larger sense, this research will provide useful information about ways through which education leaders and policymakers can work towards constructing specialised teacher professionalism; it will thus foster better quality education in Indonesia.